Blue Sky Defense for Carbon Emission Trading Policies: A Perspective on the Spatial Spillover Effects of Total Factor Carbon Efficiency - Gao, Da; Tan, Linfang; Mo, Xinlin; Xiong, Ruochan (Systems (Basel), 2023)
In the pursuit of China’s environmental targets to achieve a carbon peak by 2030 and carbon neutrality by 2060, the carbon emission trading scheme (CETs) has emerged as a critical policy instrument. Since the 14th Five-Year Plan, China has been on a two-wheel drive to prevent pollution and combat climate change and proposes to fight the Blue Sky Defense. Therefore, this study focuses on prefecture-level cities in China and employs a spatial difference-difference (SDID) model to investigate the spatial spillover effects of CETs on urban total factor carbon emission efficiency (TFCEE). Furthermore, a mediating effect model is constructed to explore the channels through which CETs influence carbon emission efficiency. The results show that (1) implementing urban CETs can significantly improve urban itself and the surrounding carbon emission efficiency. (2) The CETs can indirectly promote the improvement of carbon efficiency by optimizing the allocation of labor resources and strengthening the level of green technology innovation. (3) Compared with the cities in central and western China, implementing the CETs has a stronger promotion effect on the carbon emission efficiency of the cities in eastern China.